Práticas de letramento acadêmico de estudantes internacionais matriculados em uma disciplina de ensino/aprendizagem de português como língua adicional - Gláucio Geraldo Moura Fernandes (2021)
This research is based, theoretically and methodologically, on the sociocultural aspect of the New Literacy Studies, being concerned with academic literacy in Portuguese as an Additional Language (PLA) and paying attention to the diversity of the public participating in the study. Inserted in the area of Applied Linguistics, having as research object language as a social practice in a context in which relevant questions about the use of language arise, this research aimed to investigate literacy practices of international students linked to academic mobility programs and enrolled in a discipline focused on teaching academic writing in PLA. For this, I analyze a corpus formed by (i) a questionnaire applied to students in the initial phase of the discipline; (ii) Didactic Unit worked during the written production module; (iii) student logbooks with written notes and audio comments; (iv) recording of audio classes; (v) use of the Translog II software used to generate written records and protocols from textual production; (vi) final production of the proposed genre. The corpus was generated throughout the offer of the written production module, part of the discipline Portuguese Additional Language - Academic Writing (UNI 048). During the classes, I counted on the participation of five students, from five different countries, enrolled in the discipline. The analysis, using reflections about studies that deal with the internationalization of Portuguese and linguistic policies (OLIVEIRA, 2013; DINIZ, 2009, 2012; BARBALHO, 2007), internationalization of higher education (BIZON, 2013; MARTINEZ, 2017; KNIGHT & DE WIT, 1995), academic literacy (STREET, 1984, 2010; LEA & STREET, 1998, 2014; FIAD, 2013, 2015; LILLIS, 2001) and academic-scientific genres (ROJO 2005; BAKHTIN / VOLOSHINOV, 2010 [1929]; MATENCIO, 2013; CANAGARAJAH, 2002), showed that there is an intention when proposing a material that has a perspective focused on the production of discursive genres. However, working with academic genres from a discursive perspective proves to be an arduous task, also because certain academic genres suffer strong coercions in terms of standardization / structuring. As for my pedagogical work, it tended towards a work focused on the compositional form, that is, on the structure. With that, I believe that, throughout the classes, I emphasized a vision that privileges the models of study skills and academic socialization (LEA & STREET, 1998). It can be noted, from my point of view, that there are moments of involvement with broader issues regarding the constitution of the genre, but there are also moments when certain opportunities are ignored. Observing students' literacy practices contributes to thinking and planning PLA courses that focus on academic literacies, but the provision of a discipline will not be enough to develop a work in this area. A proposition I make is regarding the need, in the context of Higher Education, of actions for international students inserted in the Brazilian academic context that seek to foster international cooperation, the sharing of cultural experiences, the integration and learning in the community with the differences. In this sense, it is a matter of structuring policies that break with the vision of internationalization focused only on the individual benefit, starting to think of a multilingual internationalization that considers the cultural and linguistic traditions in which the literacy practices of international students are inscribed.